The Challenges for Indonesia to Integrate Dual Vocational Education and Training System - Wibowo, Radna Andi; Nyan , Myau-Lyau; Avien Christy, Nisa Novia; Albert (Journal of Technical Education and Training, 2022)
The quality of Indonesian graduates from Technical Vocational Education and Training (TVET) programs is low and does not fulfil industry requirements and competencies. This is occurring since the talents or skills required by the sector differ from those accessible on the demand Hence, developing nations require practical VET systems and dual systems. Indonesia has recently attempted to examine the Dual Vocational Education and Training system in greater detail. This study investigates the challenges encountered by Indonesia throughout the implementation of its dual VET system and how they overcame them to ensure effective delivery. Notably, the primary goal of this literature study was to provide theoretically announced and policy-relevant understandings of the obstacles or challenges that every nation would encounter while establishing a dual system. This study combines empirical survey results from Germany and Switzerland to identify significant challenges and critical success criteria for the transfer. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were used to guide the conduct of a systematic review. The results show that the direct transfer or implementing present multiple challenges and difficulties that comprise Challenges for The Public Sector and The Public-Private. On the other hand, for a successful transfer of VET tight cooperation between all stakeholders and a shared awareness and deeper knowledge of the contextual conditions in the target nation are paramount. Therefore, the question of whether the dual VET system in German or Switzerland can be directly implemented in another country, without first examining specific challenges and difficulties of each context, must be clearly and systematically considered.